Russian Translation : Theory and practice. - Maksimova, Elena (Thinking translation., 2009)
Thinking Russian Translation is a comprehensive practical course in translation for advanced undergraduate and first-year postgraduate students of Russian. The course aims to provide intensive exposure with a view to mastering translation from Russian into English while carefully analyzing the specific problems that arise in the translation process. Over 30 practical translation exercises, and further texts are analyzed in detail from a wide range of sources, including journalistic, medical, scholarly, legal and popular culture. A variety of translation issues are addressed, among them cu.